Characterization of m6A Regulator-Mediated Methylation Modification Patterns and Tumor Microenvironment Infiltration in Ovarian Cancer - Luo, Yihong; Sun, Xiang; Xiong, Jian (Frontiers in Cell and Developmental Biology, 2022)
Introduction: Studies have demonstrated the epigenetic regulation of immune responses in various cancers. However, little is known about the RNA N6-methyladenosine (m6A) modification patterns of the microenvironment (TME) cell infiltration in ovarian cancer (OC). Methods: We evaluated the correlation between m6A modification patterns and TME cell infiltration based on 459 OC samples from the Cancer Genome Atlas and Gene-Expression Omnibus database. We constructed an m6Ascore system to quantify m6A modification patterns using principal component analysis. Results: Based on unsupervised clustering, three m6A modification patterns were identified. Gene set variation analysis showed that the antigen presentation signal pathway, the NOTCH signaling pathway, and the metabolism-related pathway differed significantly across m6A modificaiton patterns. The m6Ascore is closely correlated with TME cell infiltration. OC patients with lower m6Ascores had worse outcomes. There was better risk stratification with combined m6Ascore and tumor mutation burden. The responses to immune checkpoint inhibitor treatment significantly differed between high and low m6Ascore groups. Conclusions: M6A modification plays an essential role in TME cell infiltration in OC. Evaluating the m6A modification patterns in OC patients could enhance our understanding of TME infiltration characterization and guide immunotherapy strategies.